MobBIO: A multimodal database captured with a portable handheld device - Sequeira, Ana (2014)
The authors author would like to thank Fundação para a Ciência e Tecnologia (FCT) - Portugal the financial support for the PhD grants with references SFRH/BD/74263/2010 and SFRH/BD/87392/2012